2017
DOI: 10.1016/j.tcs.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Domination number and minimum dominating sets in pseudofractal scale-free web and Sierpiński graph

Abstract: The minimum dominating set (MDS) problem is a fundamental subject of theoretical computer science, and has found vast applications in different areas, including sensor networks, protein interaction networks, and structural controllability. However, the determination of the size of a MDS and the number of all MDSs in a general network is NP-hard, and it thus makes sense to seek particular graphs for which the MDS problem can be solved analytically. In this paper, we study the MDS problem in the pseudofractal sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…It is a small-world complex network with hierarchical structure, a scale-free degree distribution with power law exponent γ ≈ 2.57, and a high clustering coefficient of C = 4/5, matching several characteristic benchmarks of real-life complex nets. Its recursive nature and the finite articulation have enabled exact analytical studies of the statistics of cycles [5], diffusion [6], percolation [3], spectral properties [7], and minimum dominating sets [8], shedding light on the analogous properties in real-life complex nets.…”
Section: Introductionmentioning
confidence: 99%
“…It is a small-world complex network with hierarchical structure, a scale-free degree distribution with power law exponent γ ≈ 2.57, and a high clustering coefficient of C = 4/5, matching several characteristic benchmarks of real-life complex nets. Its recursive nature and the finite articulation have enabled exact analytical studies of the statistics of cycles [5], diffusion [6], percolation [3], spectral properties [7], and minimum dominating sets [8], shedding light on the analogous properties in real-life complex nets.…”
Section: Introductionmentioning
confidence: 99%
“…Other than trivial results such as for paths or cycles, perhaps the most famous result is the sprawling effort over a 27 year period [18,14,8,34,2,12] to provide a complete characterisation of domination numbers for grid graphs G(n, m) of all possible sizes, consisting of 23 special cases before settling into a standard formula for n, m ≥ 16. Other results for domination include generalized Petersen graphs [41,23,39], Cartesian products involving cycles [26,9,1], King graphs [40], Latin square graphs [27], hypercubes [3], Sierpiński graphs [32], Knödel graphs [38], and various graphs from chemistry [25,30], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, these problems have become very active and have been popular research objects. Many authors have devoted their efforts to developing algorithms for the problems associated with maximum matchings [15][16][17][18][19][20], MISs [21][22][23], as well as MDSs [24][25][26][27][28]. Although scientists have made a concerted effort, solving these problems is an important challenge and often computationally difficult.…”
Section: Introductionmentioning
confidence: 99%
“…This nontrivial scale-free structure is a fundamental concept in the study of the emerging network sciences. Many previous studies have shown that the scale-free topology plays an important role in various structural [36], combinatorial [13,19,[26][27][28], and dynamical [37][38][39] properties of a graph. In the context of combinatorial aspect, it has been shown that compared with non-scale-free graphs, in scalefree networks, both the matching number [13] and the number of maximum matchings [19] are significantly smaller.…”
Section: Introductionmentioning
confidence: 99%